A theoretical overview of road hump effects on traffic noise in improving residential well-being - Bachok, Khairun Sarah Radhiah; Kadar Hamsa, Abdul Azeez; Mohamed, Mohd Zin; Ibrahim, Mansor (2016)
Previous studies have stated that an urban residential area’s living quality is threatened by noise annoyance, of which traffic noise is considered the main contributor. This paper aims to discuss if the speed-reducing benefits of existing road humps make them viable as a noise-reducing measure, particularly when the humps do not comply with existing guidelines. The methods used were a literature review and paired-sample T-tests to test the significance of changes in traffic noise at selected road humps. The literature and data showed that noise levels were still high at roads with road humps, due to the frequency of vehicle accelerations and decelerations near the road humps. The noise levels are also above the permissible noise level for Malaysian residential areas. This suggests that road humps are less viable especially when drivers change their speed of vehicles appreciably when approaching the road humps.